Catalytic Oxygenation of Hydrocarbons by Mono-mu-oxo Dicopper(II) Species Resulting from O-O Cleavage of Tetranuclear Cu-I/Cu-II Peroxo Complexes - Jurgeleit, Ramona; Grimm-Lebsanft, Benjamin; Floeser, Benedikt Maria; Teubner, Melissa; Buchenau, Soren; Senft, Laura; Hoffmann, Jonas; Naumova, Maria; Naether, Christian; Ivanovic-Burmazovic, Ivana; Ruebhausen, Michael; Tuczek, Felix (Angewandte Chemie International Edition, 2021)
One of the challenges of catalysis is the transformation of inert C-H bonds to useful products. Copper-containing monooxygenases play an important role in this regard. Here we show that low-temperature oxygenation of dinuclear copper(I) complexes leads to unusual tetranuclear, mixed-valent mu(4)-peroxo [Cu-I/Cu-II](2) complexes. These Cu4O2 intermediates promote irreversible and thermally activated O-O bond homolysis, generating Cu2O complexes that catalyze strongly exergonic H-atom abstraction from hydrocarbons, coupled to O-transfer. The Cu2O species can also be produced with N2O, demonstrating their capability for small-molecule activation. The binding and cleavage of O-2 leading to the primary Cu4O2 intermediate and the Cu2O complexes, respectively, is elucidated with a range of solution spectroscopic methods and mass spectrometry. The unique reactivities of these species establish an unprecedented, 100 % atom-economic scenario for the catalytic, copper-mediated monooxygenation of organic substrates, employing both O-atoms of O-2.
CRIS-Team WoS Importer:2021-05-14